Representasi Lingkungan dalam Sastra Indonesia: Tinjauan Literatur Review - Pamungkas, Onok Yayang; Hastangka, Hastangka; Sudigdo, Anang; Fathonah, Siti; Fauzan, Akhmad; Suroso, Eko (Jurnal Kridatama Sains dan Teknologi, 2022)
The current environmental crisis is an important issue that is the focus of research globally, including in Indonesia. Therefore, this research is an effort to explore trends in environmentally sound literary research in Indonesia. The research process was carried out by combining statistical data combined with descriptive analysis. Therefore, mixed-method research methods are considered appropriate to use.  Research data is a source of literary ecology research trends taken from the Google Scholar database. The data source is Google Scholar. Data retrieval using the Publish or Perish app. The data is taken by entering the keyword "literary ecology" in the Google Scholar database drop-down menu. Once the data is retrieved, it is then analyzed using the Vosviewer application. Vosviewer analysis can display research trends, research topic relationships, research developments from year to year, and various research information, in accordance with the research focus based on data inputted in the application The results of the study show that literary ecology research in Indonesia has only developed in at least the last five years. In quantity, the amount of literary ecology research in Indonesia is increasing. In terms of the quantity of types of relationships with various other scientific terminology, the number is still small. Meanwhile, in terms of research trends with literary ecology research topics have shown progress that continues to develop by involving other sciences. This is certainly a good development in scientific debate, because the issue of environmental crisis discussed through literary ecology involves various other scientific fields for the purpose of solving environmental problems globally. An important implication of this research is that information about literary ecology research trends in Indonesia can be an important source of knowledge to see the efforts of the Indonesian people in their participation in dealing with global environmental problems. Keywords: Literary ecology, Ecocriticalism, Literature Review, Environmental Ethics, Literary Works